Partition-associated incompatibility caused by random assortment of pure plasmid clusters. - Ebersbach, G; Sherratt, D; Gerdes, K (2005)
Summary Bacterial plasmids and chromosomes encode centromere-like partition loci that actively segregate DNA before cell division. The molecular mechanism behind DNA segregation in bacteria is largely unknown. Here we analyse the mechanism of partition-associated incompatibility for plasmid pB171, a phenotype associated with all known plasmid-encoded centromere loci. An R1 plasmid carrying par2 from plasmid pB171 was destabilized by the presence of an F plasmid carrying parC1, parC2 or the entire par2 locus of pB171. Strikingly, cytological double-labelling experiments revealed no evidence of long-lived pairing of plasmids. Instead, pure R1 and F foci were positioned along the length of the cell, and in a random order. Thus, our results raise the possibility that partition-mediated plasmid incompatibility is not caused by pairing of heterologous plasmids but instead by random positioning of pure plasmid clusters along the long axis of the cell. The strength of the incompatibility was correlated with the capability of the plasmids to compete for the mid-cell position.